2006
DOI: 10.2135/cropsci2005.10.0388
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Analysis of High Gamma‐Tocopherol Content in Sunflower

Abstract: Sunflower (Helianthus annuus L.) seeds contain alpha-tocopherol as the major tocopherol derivative, which accounts for more than 900 g kg 21 total tocopherols. However, four sources of high gammatocopherol content (.850 g kg 21 ) have been developed. First studies on the lines LG-17 and T2100 concluded that the trait in both lines was determined by recessive alleles at the Tph2 locus. The objectives of the present research were (i) to conduct an allelic study on the other two lines, IAST-1 and IAST-540, (ii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
3
25
1
1
Order By: Relevance
“…A SSR marker closely linked to the tph2 allele was identified on linkage group 8. The presence of a closely linked marker could help to increase the selection efficiency and development of sunflower genotypes with high γ ‐tocopherol contents . The sunflower line T‐589 had a higher content of β ‐tocopherol (30%) containing the tph1 gene.…”
Section: Tocopherols and Sterolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A SSR marker closely linked to the tph2 allele was identified on linkage group 8. The presence of a closely linked marker could help to increase the selection efficiency and development of sunflower genotypes with high γ ‐tocopherol contents . The sunflower line T‐589 had a higher content of β ‐tocopherol (30%) containing the tph1 gene.…”
Section: Tocopherols and Sterolsmentioning
confidence: 99%
“…Tight linkage was observed between the gene tph1 and SSR marker on linkage group LG1. It was mapped on the upper side of LG1 and co‐segregated with SSR markers ORS1093, ORS222, and ORS598 …”
Section: Tocopherols and Sterolsmentioning
confidence: 99%
“…Sunflower lines T2100 and IAST‐1 with increased levels of gamma‐tocopherol in seeds also showed increased levels of this tocopherol form in roots, leaves and pollen, though both lines differed in gamma‐tocopherol content in these tissues, particularly in pollen. Previous research has associated increased levels of gamma‐tocopherol in sunflower seeds with reduced activity at a gamma‐TMT locus, Tph2 10, 11 . Arabidopsis mutants carrying a functional null mutation of the gene encoding for gamma‐TMT27 as well as gamma‐TMT‐silenced plants of tobacco29 showed a drastic reduction in alpha‐tocopherol and a concomitant increase in gamma‐tocopherol in leaves, which is in agreement with the results of the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of beta‐tocopherol around 500 g kg −1 tocopherols are controlled by recessive alleles at a single locus named Tph1 ,6, 9 whereas levels of beta‐tocopherol over 650 g kg −1 tocopherols are produced by recessive alleles at two loci, Tph1 and MT‐2 , both of which are paralogues of MPBQ/MSBQ‐MT 10. Increased levels of gamma‐tocopherol over 900 g kg −1 tocopherols are the result of a recessive mutation in the Tph2 locus,6, 11 which has been identified as a gamma‐tocopherol methyltransferase 10. Increased levels of delta‐tocopherol are produced by epistatic interaction of Tph1, Tph2 and MT‐2 loci 12…”
Section: Introductionmentioning
confidence: 99%
“…The Tph1 gene controlling increased seed β‐tocopherol content was mapped to linkage group (LG) 1 (Tang et al, 2006; Vera‐Ruiz et al, 2006), with recessive tph1 alleles being the result of a nonlethal knockout mutation in a MPBQ/MSBQ‐MT gene (Tang et al, 2006). The Tph2 gene determining high seed γ‐tocopherol content was mapped to LG 8 (Hass et al, 2006; García‐Moreno et al, 2006) of the sunflower linkage map and was found to be a γ‐TMT gene (Hass et al, 2006). A third gene, MT‐2 , involved in modified seed tocopherol profile in sunflower was identified on LG 4 and determines very high β‐tocopherol content in combination with tph1 alleles.…”
mentioning
confidence: 99%